Supporting the Mental Health Needs of Veterans in the Metro Detroit Area - Tanielian, Terri (RAND Corporation, 2016)
Over the past decade, the government has expanded funding and services to meet increasing demand for improved veteran access to high-quality mental health services. This report describes findings from a study designed to gather information on mental health-related needs facing veterans in the Detroit metropolitan area to identify gaps in the support landscape and inform future investments for community-level resources to fill the identified gaps.